Broken and forgotten: A case of unintentionally retained foreign object. (2020) - Nguyen, Hong Loan; Herrera, Lauren Nicholas; Cheema, Ali; Sarkar, Pralay Kumar
Abstract: Central venous catheter have become ubiquitous with greater than 15 million catheter days/year in the intensive care setting alone. However, the procedure carries with it several immediate and other delayed complications that can result in significant morbidity, mortality, and increased healthcare cost. We report a rare case of significantly delayed complications associated with intravascular loss of guide wire during central venous catheter placement and its impact on patient's long term management. The case highlights not only the importance of proper technique and safety precaution in performing an increasingly common procedure, but also the need for timely identification and rectification of medical errors, especially in the context of improved physician-patient communication.